Yield and yield attributes, nutrients uptake, nitrogen-use efficiency and economics of oleiferous brassicas as influenced by time of sowing and fertility levels - RANA, D S (The Indian Journal of Agricultural Sciences, 2014)
In a field experiment conducted during the winter seasons of 1996-98 at New Delhi, indian mustard [Brassica juncea (L.) Czernj. & Cosson], karan rai or ethiopian mustard (Brassica carinata A. Braun) and gobhi sarson [Brassica napus (L.) ssp oleifera DC. var annual were evaluated for their performance under timely and late-sown conditions and fertility levels (N0, N75, N150, N75 + S30 and N150 + S30) Ethiopian mustard consistently gave the highest number of siliquae/plant (360), seeds (2.96 tonnes/ha), biological (15.36 tonnes/ha) and oil (1.18 tonnes/ha) yields, nutrient uptake (170 kg N, 12.5 kg P, 210.8 kg K and 91 kg S/ha), benefit:cost ratio (2.88), N-use efficiency (14.9 kg seed/kg N applied), apparent N recovery (101.5%) and partial factor productivity (31.8 kg seed/kg N applied). However, 1 000-seed weight (5.3 g), harvest index (21.9 %) and physiological efficiency of N (15.3kg seed/kg of N removed) were maximum in indian. mustard and number of seeds/siliqua (23.4) and oil (41.1%) and protein (22.3%) content were the highest in gobhi sarson. Delayed sowing caused significant reduction in siliquae/plant (16.5%), 1 000-seed weight (9.1 %), oil content (2.7%), seed (7.1 %), oil (9.9%) and.biological (11.0%) yields, and N (7.1 %), P (6.6%) and S (6.3%) uptake. At 2 dates of sowing, ethiopian mustard maintained its significant superiority for seed yield, but the percent reduction in yield due to delay in sowing was minimum in gobhi sarson (2.7%) and maximum in indian mustard (10.6%). Successive increase in N levels significantly increased yield and yield attributes, benefit:cost ratio, nutrient uptake except seeds/siliqua, oil content and N-use efficiency. Application of N + S increased most of the parameters over N alone.